FORMATION AND DEVELOPMENT OF ENTREPRENEURSHIP AND BUSINESS IN RUSSIA IN XVII-XXI CENTURES - S. Sazanova (Вестник университета)
The author explores the Russian business in the XVII-XXI centuries. based institutional approach, institutional factors reveals the formation and development of entrepreneurial activity.